Comparison of energy efficiency between atmospheric batch pressure-retarded osmosis and single-stage pressure-retarded osmosis - Li, Dan (2023)
Batch pressure-retarded osmosis (PRO) with varied-pressure and multiple-cycle operation using a pressurized variable-volume tank has been proposed as a high-efficiency osmotic energy harvesting technology, but it suffers scalability constraints. In this study, a more scalable batch PRO, namely, atmospheric batch PRO (AB-PRO), was proposed, utilizing an atmospheric tank to receive and store the intermediate diluted draw solution (DS) and a pressure exchanger to recover the pressure energy from the diluted DS before being recycled into the tank. Its performance was further compared with single-stage PRO (SS-PRO) at different flow schemes via analytic models. The results show that the AB-PRO with an infinitesimal per-cycle water recovery (r) approaches the thermodynamic maximum energy production under ideal conditions, outperforming the SS-PRO with lower efficiencies caused by under-pressurization (UP). However, when considering inefficiencies, a ~40% efficiency reduction was observed in AB-PRO owing to UP and entropy generation as the optimal r is no-longer infinitesimal. Nonetheless, AB-PRO is still significantly superior to SS-PRO at low water recoveries (R) and maintains a stable energy efficiency at various R, which is conducive to meeting the fluctuating demand in practice by flexibly adjusting R. Further mitigating pressure losses and deficiencies of energy recovery devices can significantly improve AB-PRO performance.